N(6)‐methyladenosine‐binding protein YTHDF1 suppresses EBV replication and promotes EBV RNA decay. (19th February 2021) - Xia, Tian‐Liang; Li, Xingyang; Wang, Xueping; Zhu, Yun‐Jia; Zhang, Hua; Cheng, Weisheng; Chen, Mei‐Ling; Ye, Ying; Li, Yan; Zhang, Ao; Dai, Dan‐Ling; Zhu, Qian‐Ying; et al.
Abstract: N 6 ‐methyladenosine (m 6 A) modification of mRNA mediates diverse cellular and viral functions. Infection with Epstein–Barr virus (EBV) is causally associated with nasopharyngeal carcinoma (NPC), 10% of gastric carcinoma, and various B‐cell lymphomas, in which the viral latent and lytic phases both play vital roles. Here, we show that EBV transcripts exhibit differential m 6 A modification in human NPC biopsies, patient‐derived xenograft tissues, and cells at different EBV infection stages. m 6 A‐modified EBV transcripts are recognized and destabilized by the YTHDF1 protein, which leads to the m 6 A‐dependent suppression of EBV infection and replication. Mechanistically, YTHDF1 hastens viral RNA decapping and mediates RNA decay by recruiting RNA degradation complexes, including ZAP, DDX17, and DCP2, thereby post‐transcriptionally downregulating the expression of EBV genes. Taken together, our results reveal the critical roles of m 6 A modifications and their reader YTHDF1 in EBV replication. These findings contribute novel targets for the treatment of EBV‐associated cancers. Synopsis: The m 6 A reader YTHDF1 promotes viral RNA degradation by recruiting RNA decay complexes, including ZAP, DDX17, and DCP2. YTHDF1 suppresses EBV lytic replication to regulate EBV infection status. m 6 A modifications are widespread in the EBV transcripts in nasopharyngeal carcinoma (NPC) cells and tissue samples. YTHDF1 suppresses EBV lytic replication. YTHDF1 promotes viral RNA decay in an m 6 A‐dependent manner by recruiting RNA degradation complexes. Abstract : The m 6 A reader YTHDF1 promotes viral RNA degradation by recruiting RNA decay complexes, including ZAP, DDX17, and DCP2. YTHDF1 suppresses EBV lytic replication to regulate EBV infection status.